A feasibility study of children's wear manufacturing by Jourdan Et Cie - Salvador, Dennis O.
This study aimed to find out the share that the buying market would give if another line of apparel would be introduced by a local garment manufacturer that produces RTW clothes. Jourdan et Cie had planned to go into new heights by means of marketing children's clothes. Interviews and market surveys were used as instruments in the study to find out whether the project wear would be feasible or not. The researcher distributed the market surveys in all sales outlets of Jourdan et Cie (JEC) in Metro Manila. The whole of Metro Manila were divided into three parts namely North sector, Central Sector, South Sector. One hundred questionnaires were distributed in each area so there were three hundred questionnaires all in all. The results were tabulated by averaging the data obtained in every sector. The results showed that the manufacturing of children's clothes by Jordan et Cie is feasible.